The use of benzodiazepines by women cared for at a Family Health Unit - Paula Adriana da Silva; Letícia Yamawaka de Almeida; Jacqueline de Souza (SciELO, 2019)
ABSTRACT Objective: Estimate the prevalence of benzodiazepine use by adult women at a Family Health Unit and identify the risk factors associated with this usage. Method: Quantitative cross-sectional study that employed secondary data developed at a Family Health Unit in the state of São Paulo, Brazil. We collected the data from the following sources: medical charts, registration forms, and the archive of prescriptions from the pharmacy at the referred health unit. We employed the chi-squared, Student's t, and Mann-Whitney tests, as well as logistic regression analysis. Results: We identified 81 benzodiazepine users amongst 1,094 adult women (7.4%). Regarding the risk factors, the comparison between the groups of benzodiazepine users (n = 64) and non-users (n = 70) showed that having a chronic disease and using other psychotropic drugs were significantly associated with the use of benzodiazepines. Conclusion: The prevalence found was lower than the described in previous studies performed in Primary Health Units. The group that must receive greater attention regarding the consumption of benzodiazepines is that of middle-aged women or older, with low education levels, and chronic illnesses.